Pengertian, hukum, macam-macam, syarat, rukun dan hikmah puasa - subhi, Irfan (Maliki Interdisciplinary Journal, 2025)
Fasting is a worship that is done by holding back hunger, thirst and lust from dawn to sunset. Fasting is also the third pillar of Islam, which is an obligation that must be carried out by Muslims. Fasting teaches a person to restrain himself from everything that can break his fast. This journal will discuss the meaning, law, requirements and types of fasting. Fasting is worship carried out to Allah by enduring hunger, thirst and anything that cancels it. The law of fasting is obligatory. However, we also need to know what fasting is obligatory, because not all fasting is considered obligatory. Fasting is divided into four types of fasting, namely obligatory fasting, sunnah fasting, makruh fasting, and haram fasting.